2001
DOI: 10.1103/physrevb.64.184114
|View full text |Cite
|
Sign up to set email alerts
|

Monoclinic phase in the relaxor-based piezoelectric/ferroelectricPb(Mg1/3N

Abstract: A ferroelectric monoclinic phase of space group Cm (M A type) has been discovered in 0.65Pb(Mg 1/3 Nb 2/3 )O 3 -0.35PbTiO 3 by means of high resolution synchrotron X-ray diffraction. It appears at room temperature in a single crystal previously poled under an electric field of 43 kV/cm applied along the pseudocubic

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
186
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(198 citation statements)
references
References 23 publications
10
186
0
2
Order By: Relevance
“…7-11͒ and PMN-xPT. [11][12][13][14][15][16] It has since been argued that monoclinic symmetry may be an important property underlying the exceptional piezoelectric response of PMN-xPT and PZN-xPT as it allows the polarization vector to rotate freely within a plane 17 rather than be restricted to a particular crystallographic axis as is the case for the higher symmetry R, T, and orthorhombic ͑O͒ phases.…”
Section: ͑Pmn-xpt͒mentioning
confidence: 99%
“…7-11͒ and PMN-xPT. [11][12][13][14][15][16] It has since been argued that monoclinic symmetry may be an important property underlying the exceptional piezoelectric response of PMN-xPT and PZN-xPT as it allows the polarization vector to rotate freely within a plane 17 rather than be restricted to a particular crystallographic axis as is the case for the higher symmetry R, T, and orthorhombic ͑O͒ phases.…”
Section: ͑Pmn-xpt͒mentioning
confidence: 99%
“…Moreover, the sequence of structural phase transitions can be easily changed by the influence of the physical parameters such as pressure, electric field and the kind of polarization [18,20,21]. For example, it was demonstrated that the previously poled PMN-35%PT solid solutions adopt the monoclinic symmetry with the Cm space group at room temperature [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent extensive experimental investigations have discovered new intermediate phases and revealed fascinating while puzzling phase behaviors around the MPBs. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Since the recent discovery of an intermediate monoclinic M A phase in PZT near its MPB, [23][24][25][26][27][28] new intermediate phases have also been discovered in PZN-xPT and PMN-xPT near their respective MPBs, namely, monoclinic M A , [8][9][10] monoclinic M C , [8][9][10][11][12] orthorhombic ͑Refs. 8 and 13-15͒ phases in PZN-xPT, and orthorhombic, 16,17 monoclinic M C , 12,[18][19][20][21] monoclinic M A , 21,22 as well as a third monoclinic M B phase ͑Refs.…”
Section: Introductionmentioning
confidence: 99%